Repleksiyon hinggil sa Neokolonyang Edukasyon: Neoliberalismong Indoktrinasyon Laban sa Mapagpalayang Pagtuturo at Kabatiran (REFLECTIONS ON NEOCOLONIAL EDUCATION: Neoliberal Indoctrination against Liberating Pedagogy and Knowledge) - San Juan, Epifanio Jr. (Social Sciences and Development Review, 2023)
Contextualized in the history of U.S. colonization of the Philippines, the current educational system that sustains the subjugation of the dominated stems from the white-supremacist ideology of pacification institutionalized throughout the dependent formation. Key here is the imposition of the colonizer’s language. With the cooptation of the feudal oligarchy, the colonial state apparatus promoted individualist-consumerist disposition and careerism. This coalesced with the inherited client-patron pattern prevailing in the countryside. This subservience of Filipino minds and bodies continues with the return of U.S. military bases and the reenforcement of a comprador-subaltern sense of inferiority, alongside a resurgence of national-popular resistance. Contradictions within the imperial hegemony have allowed the rise of critical pedagogy in the middle stratum that may challenge neoliberal norms, given the intensifying crisis of U.S. capitalism and the challenge of China and other third-world revolutionary movements.